THROMBOCYTOPENIC PURPLE - Umarkulov Muhtorali; Xodjamberdiyev Akramjon; Karimov Salohiddin (Scholar Express Journals, 2021)
Thrombocytopenic purpura (Werlhof's disease, benign thrombocytopenia) is a hematological pathology characterized by a quantitative deficiency of platelets in the blood, accompanied by a tendency to bleeding, the development of hemorrhagic syndrome. With thrombocytopenic purpura, the level of platelets in the peripheral blood drops significantly below the physiological level - 150x109 / l with a normal or slightly increased number of megakaryocytes in the bone marrow. In terms of the frequency of occurrence, thrombocytopenic purpura ranks first among another hemorrhagic diathesis
Keywords: thrombocytopenias; Isoimmune; Transimmune; angiotrophic